Decay of phosphorescence and delayed fluorescence of organic materials - Luka, A K; Baghel, R N; Chandra, V K (Recent Research in Science and Technology, 2012)
The Present paper reports the decay of phosphorescence and delayed fluorescence of organic material poly (2,7-(9,9-bis(2-ethyl-hexyle-flourene) (PF2/6). On the basis of the rate equation for the generation , recombination and diffusion of triplet excitons expressions are derived for the decay time of phosphorescence and delayed fluorescence of organic materials. The lifetime of phosphorescence is comes out to be twice the decay time of delayed fluorescence. The intensity of phosphorescence depends linearly on the intensity of the laser light used for exciton , however the intensity of light depends quadritically on the intensity of the laser light used for excitation. A compression is made between the theoretical and experimental results, in which a good agreement is found.